Schwanomma of the parotid gland and its presentation - Madhu, C. P.; Venugopal, Swetha (International Surgery Journal, 2016)
Our objective is to present a very rare clinical case of intraparotid facial nerve schwannoma that clinically presented as an asymptomatic parotid tumor, cystic neoplasm of the left parotid gland and was diagnosed after histopathology as schwanomma of the facial nerve. Another purpose is to discuss diagnostic possibilities, appropriate planning for the management and predictive outcomes of surgical management. A clinical case of a patient with an asymptomatic parotid mass diagnosed as a facial nerve schwannomaintraoperatively is presented. The patient’s presentation and the diagnostic procedures, surgery and the follow up procedures are discussed. Intraparotid facial nerve schwannoma is an extremely rare entity and rarely diagnosed preoperatively. Management of intraparotid facial nerve schwannomas (IFNS) is very challenging because the diagnosis is often made intraoperatively and in most cases resection can lead to severe facial nerve (FN) paralysis with significant aesthetic consequences. Imaging studies and fine-needle aspiration cytology are not always helpful in preoperative diagnosis.